Empowering Rural Prosperity: Strategies for Sustainable Social Welfare Through the Tourism Village Priority Program in West Java Province - Alia, Siti; Wahyu, Fitri Pebriani; Septiadi, Muhammad Andi; Sule, Babayo (Publica: Jurnal Pemikiran Administrasi Negara, 2024)
This research conducts a qualitative analysis of the challenges and intricacies involved in establishing sustainable tourism villages in Indonesia, with a specific focus on West Java Province, using the village of Alam Endah as its subject. The study's core findings underscore the pivotal role of human resource relations in driving the development of tourist villages, emphasize the importance of clear regulatory frameworks and legal structures for sustainable growth, and highlight the effectiveness of strategic marketing in enhancing the attractiveness of these villages. Additionally, it underscores the significant impact of sustainable tourism village development in uplifting the welfare of local communities. By weaving these elements together and fostering strong interconnections among them, this research provides a comprehensive roadmap for the sustainable development of tourism villages, offering lasting economic, social, and environmental benefits to the region.